2014
DOI: 10.1177/0738894214530832
|View full text |Cite
|
Sign up to set email alerts
|

What drives ethnic terrorist campaigns? A view at the group level of analysis

Abstract: This article examines the drivers of terrorist campaigns waged specifically for the sake of ethnic identity groups. Terrorism scholarship has generally overlooked the ethnic dimension that some terrorist campaigns have in favor of building or testing theories applicable to all terrorist violence, regardless of ideological orientation. The research that does address ethnic terrorism attributes it either to a broad and vague notion of nationalism or to factors that might be idiosyncratic of a small number of cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
0
16
0
2
Order By: Relevance
“…Although ethnic identification has been recognized as a major source of extremist behavior (Masters, 2008), research on ethnic extremism is still underdeveloped. Certainly, the motivation of ethnic extremists is somewhat different from other cases of extremism or terrorism: the core grievances of ethnic extremism are based more on dissatisfaction in reference to the political goals of their national group than to other forms of deprivation, such as economic grievances (Boylan, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ethnic identification has been recognized as a major source of extremist behavior (Masters, 2008), research on ethnic extremism is still underdeveloped. Certainly, the motivation of ethnic extremists is somewhat different from other cases of extremism or terrorism: the core grievances of ethnic extremism are based more on dissatisfaction in reference to the political goals of their national group than to other forms of deprivation, such as economic grievances (Boylan, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these data are in line with previous findings regarding observed terrorist actions: ethnic polarization increases the probability of terrorism (Danzell, Yeh, & Pfannenstiel, 2019); this is highly relevant in the Serbian context because Serbs and Albanians in Preševo Valley live in spatially distinct communities. Psychological underpinnings of this connection are the political grievances experienced by the members of an ethnic minority group toward the majority group (Boylan, 2016); these grievances are often accompanied by feelings of political exclusion and discrimination (Hansen, Nemeth, & Mauslein, 2018). Both of these processes are congruent with the characteristics of Serbian–Albanian relations in the previous decades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also presents an interesting juxtaposition to work on ethnic violence. It has been found that economic grievances do not generally propel ethnic terrorist violence after controlling for other relevant factors (Boylan ), but in the Catalan case, they do influence the secessionist movement, at least as defined in terms of fiscal frustrations.…”
Section: Resultsmentioning
confidence: 99%
“…This logic is also informed by the body of literature on ethnic outbidding and political violence (Bakke et al, ; Bloom, ; Boylan, ). The theory posits that ethnic elites adopt violent tactics to differentiate themselves from similar others within a competitive nationalist movement, particularly when the pursuit of power intensifies between them, to garner public support and resources (Reinares, , p. 127).…”
Section: Intensity Of Communicating To the European Unionmentioning
confidence: 99%